Accounting as a tool of State governance: The tutelage system of 'Free Africans' in Brazil between 1818 and 1864. (August 2019) - Silva, Adriana Rodrigues; Rodrigues, Lúcia Lima; Sangster, Alan
Through the theoretical lenses of Foucault's governmentality, Latour's action at a distance and Althusser's ideology theory, this article shows how accounting regulations allowed the Brazilian government to exercise control over the tutelage system of former slaves ('Free Africans') between 1818 and 1864. It finds that the measures undertaken to reinforce the accounting regulations permitted the Brazilian government to control 'Free Africans' at a distance while minimizing interference in this process from a British government intent upon abolishing slavery.